(untitled) (Forum Penelitian Agro Ekonomi, 2021)
Indonesia is one of the populous countries in the world, but lack in quality approach compared to other countries. The straight forward indicators used to find this quality are the figures of absolute poverty, corruption level, and weakness of people’s socio-cultural capital. Population quality should be viewed comprehensively which include physical number, economic, social, politic, and environment. This approach should be well applied to formulate development planning for population quality, particularly consideration about socio-cultural values inherent in the community. The socio-cultural value dimension will strongly determine the progress of the development and the level of the people’s progress in either small or big communities. A more complete and stronger value element, specifically for composite value component, will determine the level of people’s quality, especially when someone looks at its self-support, justice, solidarity, and sustainability dimensions and generation by generation.